KEBIJAKAN MANAJEMEN DAN REAKSI CUSTOMER TERHADAP PENERAPAN GREEN HOTEL (Studi Kasus pada Harris Hotel & Conventions di Kota Malang) - Putri, Lily Harlina (Profit: Jurnal Adminsitrasi Bisnis, 2020)
This research is intended to indetify the reason of management for applying green hotels concept, to describe policy of management related green hotels, to analyse the obstacle that will face, to know well positive impact that will get and to explore customer reaction regarding green hotels implementation in Harris Hotels & Conventions. The researcher use describtions methode with qualitative approach, also use primary data and secondary data that was collected by observation technique, interview, and documentation. This interview was conducted to 5 persons from hotels management and 15 persons from customer. The result of this research show that The Haris Hotels implement green concept due to goverment regulation and desire to do continues environment fundamental. Harris Hotel & Conventions Malang make some policy base on building side, efficiency of energy, product selection and waste management which follow standart of Green Hotels concept, except policy of water efficiency that not yet reach maximum result. There are 5 obstacles that will face and 2 positive impact that will get from green hotel concept implementation. Beside, customer reaction  tend to support if Harris Hotels & Conventions Malang become green hotels.